From Politics to Education: Nurcholish Madjid and the Reform of Education In Indonesia - Mushlihin Amali (Universitas Negeri Jakarta, 2019)
This paper attempts to understand Nurcholish Madjid’s Islamic education reform. After the death of Nurcholish Madjid, his education appears as a significant human capital investment which might become the instrument which constantly keep Nurcholish Madjid’s legacies alive, developed, and disseminated through times. Apart from this fact, Nurcholish Madjid’s Islamic education reform has not been yet the main focus of previous researches. Focusing on Nurcholish Madjid’s Islamic education reform, this paper looks at the educational activities of Nurcholish Madjid mainly in IAIN-UIN Jakarta and Paramadina. In this regards, this paper investigates Nurcholish Madjid’s Islamic education reform and the contexts within which it was developed. This investigation provides an insight to the discussion of the subject which tries to answer the questions of what kind of ideas which were developed by Nurcholish Madjid to reform Islamic education in Indonesia; how he defined, interpreted, and applied the ideas for the development of Islamic education in Indonesia. Eventually this paper suggests that in teaching and understanding Islam, Nurcholish Madjid obviously treated Islam not only as a religion, but also as a historical, sociological, and anthropological phenomenon which must be studied in an open, democratic, participatory, pluralistic, and inclusive way.